The importance of electronic commerce between the inevitability of electronic payment methods and the obstacles to their application in Algerian banks - فضيلة بوطورة; نوفل سمايلي (White Nile Journal for Studies and Research, 2023)
This study aimed to identify the importance of electronic commerce transactions. With the recent technological developments, including the Internet, electronic practices emerged that affect its purchasing decisions. The study showed the role of electronic payment methods in financing electronic commerce and marketing electronic services to banks, as information and communication technology has also radically changed the work of banks, making them develop their services progress from traditional methods to modern electronic methods accompanying the digital age, to contribute to their electronic services in activating trade Accordingly, the study recommended the necessity of developing banking services in a way that suits the requirements of electronic commerce in Algeria, so that the national economy can access the digital economy and benefit from international developments in this regard. Key words: E -commerce, e -marketing, electronic payment means, obstacles